2018
DOI: 10.1371/journal.pone.0192627
|View full text |Cite
|
Sign up to set email alerts
|

Trend of estimated glomerular filtration rate during ombistasvir/paritaprevir/ritonavir plus dasabuvir ± ribavirin in HIV/HCV co-infected patients

Abstract: The renal function is a key-issue in HIV/HCV co-infected patients, nevertheless, it has not established so far whether HCV treatment with new direct acting agents could impact on estimated glomerular filtration rate (eGFR) variations. In the present work, we examined the real-life data on renal function that have been prospectively collected in the SIMIT compassionate-use program of ombitasvir/paritaprevir/ritonavir plus dasabuvir (OBV/PTV/r + DSV) in 144 HIV/HCV genotype 1 co-infected patients. The population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…21 This corresponds to about 5% decline in patients with normal eGFR, and this 5% decline marker was also be used in previous study for HCV infected patients. 22 A longitudinal, observational study of chronic hepatitis C patients from multiple centers of North America and Europe (HCV-TARGET) by Saxena et al reported that patients with eGFR ≤ 45 mL/min/1.73m 2 more frequently experienced worsening renal function when they were treated with SOF-based regimen. 23 However, the major regimens of HCV-TARGET were SOF/simeprevir (SMV), SOF/RBV, SOF/pegylated interferon (PEG)/RBV, or SOF/SMV/RBV, and the rates of SVR12 were only 82%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 This corresponds to about 5% decline in patients with normal eGFR, and this 5% decline marker was also be used in previous study for HCV infected patients. 22 A longitudinal, observational study of chronic hepatitis C patients from multiple centers of North America and Europe (HCV-TARGET) by Saxena et al reported that patients with eGFR ≤ 45 mL/min/1.73m 2 more frequently experienced worsening renal function when they were treated with SOF-based regimen. 23 However, the major regimens of HCV-TARGET were SOF/simeprevir (SMV), SOF/RBV, SOF/pegylated interferon (PEG)/RBV, or SOF/SMV/RBV, and the rates of SVR12 were only 82%.…”
Section: Discussionmentioning
confidence: 99%
“…In human immunodeficiency virus infected patients, a rapid eGFR decline is generally defined by a reduction in eGFR > 5 mL/min/year in patients with baseline eGFR > 90 mL/min 21 . This corresponds to about 5% decline in patients with normal eGFR, and this 5% decline marker was also be used in previous study for HCV infected patients 22 …”
Section: Discussionmentioning
confidence: 99%
“…In the univariate analysis, we identified a relation between years of treatment with INI and eGFR reduction, while it was not observed in other ART regimens. Notably, both elvitegravir/cobicistat and dolutegravir have been associated with increased creatinine levels—though without a worsening of renal function—due to the inhibition of creatinine tubular secretion [ 20 , 27 29 ]. However, as shown in the multivariate analysis, higher VCY—and not years of exposure to INI—was retained as the predictor of eGFR reduction, thereby confirming the significant role of HIV replication in eGFR decline in the PHIV population studied.…”
Section: Discussionmentioning
confidence: 99%